Hardtank® technology in extraction of caffeine and chlorogenic acid from coffee: analysis of chemical composition and antioxidant properties of coffee beverages - Kowalski, Radosław; Belniak, Kamil; Kowalska, Grażyna; Włodarczyk-Stasiak, Marzena; Mazurek, Artur; Baj, Tomasz (Frontiers in Chemistry, 2025)
IntroductionHardtank® is a pressure-modulated, solvent-free cold extraction that shortens brewing while maximizing bioactive recovery from roasted coffee.MethodsWe produced a Nitro Cold Brew beverage from roasted Yellow Bourbon beans using Hardtank® (550 g : 10,000 mL water, 30 min, 0.3–1.5 bar) and compared its composition and antioxidant activity with laboratory extracts from roasted and green beans obtained by hot water infusion (93 °C, 5 min) and by methanol extraction (70% reflux, 2 h; 100% reflux, 2 h; 70% shake, 5 min). We measured caffeine, chlorogenic acid (and derivatives), total phenolics, total flavonoids, and antioxidant activity by the ferric reducing antioxidant power and DPPH radical tests, expressed as Trolox equivalents.Results and discussionNitro Cold Brew contained 375.8±2.4 mg phenolics + flavonoids per 100 mL, 72.4±1.1 mg caffeine per 100 mL, and 78.2±2.3 mg chlorogenic acid per 100 mL, with ferric reducing antioxidant power 27.9±0.5 mM and DPPH 11.7±0.6 mM. Using 70% methanol reflux as the 100% reference, Hardtank® achieved 135.3% for phenolics + flavonoids, 119.7% for caffeine, and up to 172.3% for chlorogenic acid. Overall, Hardtank® yielded a ready-to-drink coffee with bioactive and antioxidant profiles comparable to or better than laboratory reflux extracts, while operating rapidly and without organic solvents, indicating promise for scalable production of functional coffee beverages.